IS THE PHYSICIAN A PERSON EQUIVALENT TO A PUBLIC SERVANT AND THE SPECIAL ENTITY OF FAILURE TO PERFORM OFFICIAL DUTIES ACCORDING TO THE CRIMINAL CODE OF THE REPUBLIC OF LITHUANIA? - Amsiejute, Ausrine (European Scientific Journal, ESJ, 2014)
The author analyzes in the article the concept of a person equivalent to a public servant defined in paragraph 3 Article 230 of the Criminal Code of the Republic of Lithuania, in order to determine if a physician who has improperly provided individual health care services through negligence is considered to be a person equivalent to a public servant for the purpose of Article 230 of the Criminal Code of the Republic of Lithuania, i.e. if he can be the entity of failure to perform official duties (Article 229 of the Criminal Code of the Republic of Lithuania).